1986
DOI: 10.1002/ajh.2830230203
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐associated immunoglobulins IgG, IgM, IgA and complement C3 in immune and nonimmune thrombocytopenic disorders

Abstract: A two-stage radioactive antiglobulin test--using unlabelled antisera specific for IgG, IgA, IgM and C3 followed by binding of 125I-staphylococcal protein A--was applied to determine platelet-associated immunoglobulins (PAIg) and complement (PAC3) in thrombocytopenias of various etiologies. One hundred and one patients with immune thrombocytopenia (chronic autoimmune, 48; acute autoimmune, 37; Evans syndrome, nine; connective tissue diseases, seven) and 20 patients with presumed nonimmune thrombocytopenia (bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 30 publications
4
10
0
1
Order By: Relevance
“…Kelton et al [9] compared four different types of Phase II assays prospectively in patients in whom TP was caused by both immune and nonimmune conditions and showed that, while highly sensitive, these assays lacked sufficient specificity to be clinically useful. The findings in other studies were similar, showing an overall sensitivity of 76-91%, and specificity of 12-27%, for Phase II assays [10][11][12].…”
Section: Introductionsupporting
confidence: 73%
“…Kelton et al [9] compared four different types of Phase II assays prospectively in patients in whom TP was caused by both immune and nonimmune conditions and showed that, while highly sensitive, these assays lacked sufficient specificity to be clinically useful. The findings in other studies were similar, showing an overall sensitivity of 76-91%, and specificity of 12-27%, for Phase II assays [10][11][12].…”
Section: Introductionsupporting
confidence: 73%
“…A positive correlation between P-selectin-positive platelets and PAIgG was demonstrated previously, suggesting that activated platelets bind more antibodies than non-activated platelets [10]. Levels of PAIgG are inversely correlated with platelet counts [11,12]. We therefore assume that our cases with severe thrombocytopenia had high PAIgG levels.…”
Section: Discussionsupporting
confidence: 66%
“…Both humoral and cell mediated mechanisms have been described, but the role of the complement system has not been well defined (McMillan 2000). Limited studies of plasma complement deficiencies in patients with ITP (Trent et al, 1980; Ohali et al, 2005) and elevated levels of platelet associated complement, particularly C3 (Kayser et al, 1983; Foster et al, 1989; Panzer et al, 1986) have been reported. The observed association between platelet associated IgG/IgM and C3 suggests the potential for classical pathway complement activation on the platelet surface.…”
Section: Complement Activation On Platelets In Autoimmune Disordersmentioning
confidence: 99%